2007
DOI: 10.1002/cncr.23061
|View full text |Cite
|
Sign up to set email alerts
|

Emerging issues in smoking among adolescent and adult cancer survivors

Abstract: The number of cancer survivors is significantly increasing, thereby prioritizing the importance of identifying and preventing adverse health outcomes within this high-risk population. Cigarette smoking is of particular salience as it places both adolescents and adults with a cancer history at risk for various health problems, including second malignancies. The purpose of this article is to provide a comprehensive review of the smoking literature as it relates to adolescents and adults on-treatment and survivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 169 publications
(168 reference statements)
2
55
0
2
Order By: Relevance
“…October 22, 2013 risk-counseling interventions can reduce smoking risk among adolescents with a history of cancer for up to a year after the intervention. [630][631][632][633] A comparison of preadolescents undergoing cancer therapy to a similarly aged population without cancer found that the cancer patients were more likely to recall messages about the negative health effects of smoking and to have smoking bans in place at home. 634 In contrast, preadolescents with cancer were less likely to report receiving messages from their physicians about not smoking, a missed opportunity to improve care.…”
Section: Smoking Prevention and Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…October 22, 2013 risk-counseling interventions can reduce smoking risk among adolescents with a history of cancer for up to a year after the intervention. [630][631][632][633] A comparison of preadolescents undergoing cancer therapy to a similarly aged population without cancer found that the cancer patients were more likely to recall messages about the negative health effects of smoking and to have smoking bans in place at home. 634 In contrast, preadolescents with cancer were less likely to report receiving messages from their physicians about not smoking, a missed opportunity to improve care.…”
Section: Smoking Prevention and Cessationmentioning
confidence: 99%
“…Klosky et al 630 recently published an excellent review of smoking cessation interventions and the use of pharmacotherapy for smoking cessation among survivors of cancer diagnosed in adolescence and young adulthood. Collaborating with the Childhood Cancer Survivor Study, Emmons and colleagues, 635 in a randomized trial among adult survivors of childhood cancer, reported that survivors receiving peer counseling by telephone had a significantly higher rate of smoking cessation at 12 months than those attending a self-help group (15% versus 9%, respectively).…”
Section: Smoking Prevention and Cessationmentioning
confidence: 99%
“…Tobacco use poses a substantial health hazard to cancer survivors [6,7], including an increased risk of subsequent malignancies [8]. The estimated smoking prevalence among cervical cancer survivors exceeds 40 % compared with 14 % among breast cancer survivors, 12 % among colorectal cancer survivors [9,10], and 18 % among the general population of US women [11].…”
Section: Introductionmentioning
confidence: 99%
“…6 The Cancer review article also reports that "psychologic distress is a well-established factor that influences smoking among adolescents." 7 Although the findings are mixed, evidence suggests that survivors of childhood cancer experience greater levels of psychologic distress in adolescence and young adulthood than do unrelated or sibling controls, thus placing them at high risk for smoking onset and progression. 8 …”
Section: Current Smoking Rates Among Childhood Survivorsmentioning
confidence: 99%